Non-intrusive eye gaze direction tracking using color segmentation and Hough Transform - Bong, David B L; Lim, Kok Houi (IEEE, 2007)
This paper presents a method to detect and track the movement of the eye in a controlled context based on image processing techniques with minimal hardware support. Primary image processing techniques used in this paper are color segmentation and Hough Transform for circle detection. This system is capable of detecting the movement of the eye and its direction with reasonable accuracy.